Genesis of the national pharmaceutical legislation on the territory of modern Ukraine between IX and early XX centuries: historical and legal aspects - O. H. Aleksieiev (Zaporozhye State Medical University, 2021)
The aim of the paper is to elucidate the genesis and early development of the national pharmaceutical legislation on the territory of modern Ukraine between IX and early XX centuries taking into account historical and legal aspects. Materials and methods. The research was carried out with the use of methods of analysis and synthesis, as well as historical, and comparative and legal methods. Results. The regulation of relations that arose during the production or sale of medical drugs has always been subject to the close attention of the state, even before pharmacy became separated frommedicine. This attitude is explained primarily by the public perception of drugs as a means of possible harm to health and life-threatening. The issue of legal regulation of pharmaceutical activities should be studied from the standpoint of linguistic analysis of this term, since the Greek word pharmacon means medicine or poison. Realizing this, different countries and their institutions at different historical stages of their existence have always tried to define the legal framework of the pharmaceutical business - to outline its powers, competence and responsibility. Conclusions. The results of the historical and legal analysis show that the issue of proper suply of the population (or, at different historical stages, its separate strata) has always been under the close attention of the state. State bodies have always been paid special attention to the quality of medicines and professional training of pharmaceutical workers.